2014
DOI: 10.1007/s12098-014-1631-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Overuse as a Risk Factor for Candidemia in an Indian Pediatric ICU

Abstract: This information on pediatric candidemia could be used to devise locally-tailored strategies for identifying at-risk patients, underline the importance of routine antifungal susceptibility testing and formulate appropriate guidelines for management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…as the 2nd most common cause of BSI in PICU. Observed candidemia rates in authors' setting were probably due to the greater use of broad-spectrum antibacterial agents, invasive devices, more extensive surgical procedures and the use of advanced life support in various critical and immunosuppressed patients as has been shown in a previous studies [30,31]. Similar to authors' findings, HAIs due to Candida spp.…”
Section: Etiology Of Bsi/blood Culture Isolatessupporting
confidence: 87%
“…as the 2nd most common cause of BSI in PICU. Observed candidemia rates in authors' setting were probably due to the greater use of broad-spectrum antibacterial agents, invasive devices, more extensive surgical procedures and the use of advanced life support in various critical and immunosuppressed patients as has been shown in a previous studies [30,31]. Similar to authors' findings, HAIs due to Candida spp.…”
Section: Etiology Of Bsi/blood Culture Isolatessupporting
confidence: 87%
“… 16 A study in Hong Kong found that candidaemia occurred in patients within 6 days of ICU admission, and more than 97.0% of patients infected with fungi of Candida species had received >48 hours of antibiotic treatment. 64 Overuse and prolonged use of broad-spectrum antibiotics have been closely associated with candidaemia in China and India, 65 66 so it is reasonable to suspect a link between overuse of broad-spectrum antibiotics and early-onset of candidaemia after ICU admission. Regardless of geographical differences, most patients with IC received broad-spectrum antibiotic treatment prior to candidaemia onset in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Several well‐defined factors have been associated with increased risk of candidemia . In a prospective, multicentre, surveillance study of candidemia in children from 23 hospitals in 8 Latin America countries, the main risk factors in neonates were prematurity, ICU admission, parenteral nutrition, respiratory disease and mechanical ventilation, and in children malignancy, neutropenia, neurological disease and previous use of corticosteroids .…”
Section: Risk Factors For Development Of Candidemiamentioning
confidence: 99%
“…Several well-defined factors have been associated with increased risk of candidemia. 15,23,29,38,[44][45][46][47][48][49][50][51][52][53] In a prospective, multicentre, surveillance study of candidemia in children from 23 hospitals in 8 Latin America countries, the main risk factors in neonates were prematurity, ICU admission, parenteral nutrition, respiratory disease and mechanical ventilation, and in children malignancy, neutropenia, neurological disease and previous use of corticosteroids. 54 Regarding parenteral nutrition, a retrospective, medical record review of 286 adults who received parenteral nutrition for >72 hours showed that 4.9% were diagnosed with new-onset candidemia.…”
Section: Ris K Fac Tor S For De Velopment Of C Andidemiamentioning
confidence: 99%